Using vignettes to understand intra-household decision-making - Doss, Cheryl (International Food Policy Research Institute, 2017)
Presented by Cheryl Doss (Oxford University), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.